Dry erosion wear performance of Inconel 718 microwave clad. (November 2014) - Zafar, S.; Bansal, A.; Sharma, A. K.; Arora, N.; Ramesh, C. S.
<x content-type="archive" xml:space="preserve">Abstract</x> This paper reports on the dry erosive wear performance of Inconel 718 clads deposited on SS-304 substrates through microwave hybrid heating technique. Clads were deposited using a domestic microwave applicator at 2·45 GHz and 900 W. The microstructural observations of the Inconel 718 clad indicate good metallurgical bonding with the substrate and revealed no visible interfacial cracking. The microhardness of the clads was assessed using a Vicker's microhardness tester and the average microhardness in the clads was 564±22 HV. Erosive wear performance of the clads was evaluated using an air jet erosion test setup as per ASTM G76 standard. The effect of varying impact angle was studied; the results have been discussed with the help of SEM images of the worn surfaces. It was observed that the improved erosive performance of the Inconel 718 clads was due to presence of strengthening intermetallic phases (Ni3Ti, Ni3Al) in the tough Ni–Fe–Cr matrix.